"You deserve mob justice too": discursive justifications of mob (in)justice on social media in Africa - Addadzi-Koom, Maame Efua (International journal of law, crime and justice, 2024)
This paper explores how social media discourses justify mob justice to fuel its perpetration in Africa. It asks, what discursive strategies and patterns rationalise mob justice in social media discussions? It relies on 319 mob-justice-related tweets between 2018 and 2022 across seven African countries to identify five main discursive strategies: normative discourses, exception discourses, discourses of slow or failed criminal justice system, culture of violence discourses and banter discourses. The findings contribute to our understanding of the form mob justice discourses take on social media to incite traditional mob justice on the continent. It recommends appropriate state-centred legal responses to inciting mob justice on social media while respecting citizens’ freedom of expression.